Onion Bulb Extract Downregulates EGFR/ERK1/2/AKT Signaling Pathway and Synergizes With Steroids to Inhibit Allergic Inflammation - El-Hashim, Ahmed Z.; Khajah, Maitham A.; Orabi, Khaled Y.; Balakrishnan, Sowmya; Sary, Hanan G.; Abdelali, Ala A. (Frontiers in Pharmacology, 2020)
The treatment of allergic diseases, such as asthma, with both conventional and novel therapies presents a challenge both in terms of optimal control and cost. On the other hand, traditional based therapies, utilizing natural products such as onion, have been in use for centuries with demonstrated efficacy and safety. Treatment with onion bulb extract (OBE) inhibited the house dust mite (HDM)- induced increased phosphorylation of EGFR (117.5 ± 21.4 vs 296.7 ± 11.1 %), ERK1/2 (72.8 ± 17.5 vs 234.0 ± 35.6 %) and AKT (129.4 ± 16.6 vs 243.0 ± 13.1 %) which resulted in the inhibition of HDM-induced increase in airway cellular influx (3.3 ± 0.7 vs 11.0 ± 2.0 × 105 cells/ml), perivascular and peribronchial inflammation (2.7 ± 0.3 vs 4.2 ± 0.2; cellular infiltration score), goblet cell hyper/metaplasia (2.3 ± 0.5 vs 4.0 ± 0.3; mucous intensity score), and also inhibited ex vivo eosinophil chemotaxis (3.6 ± 0.4 vs 16.5 ± 2.4 × 104). Moreover, treatment with a combination of a low dose OBE and low dose dexamethasone resulted in a significant inhibition of the HDM induced cellular and histopathological changes, perivascular and peribronchial inflammation (2.3 ± 0.1 vs 4.5 ± 0.2; cellular infiltration score), goblet cell hyper/metaplasia (2.2 ± 0.4 vs 4.2 ± 0.2; mucous intensity score) and the pERK1/2 (80.0 ± 16.1 vs 319.1 ± 10.4 %) levels whereas neither treatment, when given alone, had any discrenable effects. This study therefore shows that inhibition of the EGFR/ERK1/2/AKT-dependent signaling pathway is one of the key mechanisms by which OBE mediates its anti-inflammatory effects in inflammatory diseases such as asthma. Importantly, this study also demonstrates that combining OBE with steroids results in significantly enhanced anti-inflammatory effects. This action may have important potential implication for future asthma therapy.